Effect of Exogenous Ethylene Gas During Ripening Process on “Thach That” Persimmon Quality - Nguyen, Thi Hanh; Vu, Thi Nga; Nguyen, Van Hung (Old Journal, 2019)
Persimmon is an important fruit plant that has been grown for a long time in Vietnam. However, if persimmon fruit is ripen naturally, acrid taste will appear and the fruit could not be edible. The purpose of this study was to reduce the tannin presence in persimmon fruit by using exogenous ethylene gas at different concentrations and times during ripening process. The variation of some quality indicators of persimmon fruits were then investigated during storage. As results, persimmon fruit treated with ethylene at 80 ppm for 12–24 hours obtained the best effect, in which tannin content decreased significantly. In addition, the quality of persimmon fruit varied in the desired direction.